The Regularity of Rhythmic Primes Influences Syntax Processing in Adults. Issue 3 (3rd July 2019) - Canette, Laure-Hélène; Bedoin, Nathalie; Lalitte, Philippe; Bigand, Emmanuel; Tillmann, Barbara
ABSTRACT: Recent research has shown that auditory rhythmic stimulation improves subsequent syntax processing of speech in children with and without developmental language disorders. Sensitivity to grammatical errors is enhanced after regular rhythmic primes in comparison to irregular ones. Our present study investigated this rhythmic priming effect in healthy adults by using subtle grammatical errors as targets, aiming to fit with the high linguistic level of the participants. We also assessed whether participants' sensitivity to rhythmic priming on syntax processing was related to self-reported rhythmic skills and musical habits. Participants listened to rhythmic regular or irregular primes followed by blocks of six grammatically correct or incorrect sentences. Participants provided grammaticality judgments on each of the sentences, and response accuracy was analyzed. Furthermore, participants filled out a questionnaire about their musical skills, listening habits and music experience. Results revealed better grammaticality processing after regular rhythmic primes in comparison to irregular ones in healthy adults. Moreover, self-reported individual characteristics related to (1) rhythmic processing and synchronization, (2) amount of daily exposure to music, and (3) social bonding, contributed to significantly predict the rhythmic priming effect. Our findings confirm the influence of temporal regularities of musical primes on subsequent syntax processing, even when syntax processing is automatized (as in healthy young adults), and they point to inter-individual differences modulating the strength of this priming effect. We discuss results within the framework of the Dynamic Attending Theory suggesting that regular rhythms orient attentional resources over time, improving the processing of event structures, including for speech.